Association between vitamin d and obesity related adipokines with breast cancer occurrence among women patients in Kelantan - Zahali, Zunura'in (2022)
Breast cancer is a common carcinoma diagnosed among women worldwide as well as Malaysia. Numerous studies reported the association between vitamin D and obesity related adipokines with breast cancer development, yet the possible roles of these risk factors remain scarce. Hence, the objective of this study was to determine the association between serum vitamin D and obesity related adipokines (HMW adiponectin and visfatin) with the development of breast cancer. This study was carried out in Kelantan, Malaysia from July 2014 until June 2017. A case-control study was conducted as a baseline recruitment and continued with follow-up of breast cancer women at 18 months post-diagnosis. At baseline 78 newly-diagnosed breast cancer patients and 85 healthy women aged 21 to 59 years old enrolled in this study. Data collection consisted of socio-demographics, reproductives history, anthropometrics and blood pressure measurement, as well as clinical biochemistry analysis. Multiple logistic regression analysis showed that cotinine (OR = 1.22; 95% CI: 1.02, 1.48), waist circumference (WC) (OR = 1.10; 95% CI: 1.02, 1.20), trigliseride (TG) (OR = 4.93; 95% CI: 1.83, 13.2) and fasting glucose (OR = 1.90; 95% CI: 1.25, 2.89) were significantly associated with increased risk of breast cancer. Serum vitamin D (OR = 0.89; 95% CI: 0.83, 0.95) and high molecular weight (HMW) adiponectin (OR = 0.76, 95% CI: 0.59, 0.98) were significantly related with decreased risk of breast cancer development. However, there was no significant association between Vitamin D receptor (VDR) polymorphism (FokI, BsmI and TaqI) with breast cancer was observed.